Risk Factors for Antiphospholipid Antibodies and Antiphospholipid Syndrome - Aguirre del-Pino, Rodrigo; Monahan, Rory C.; Huizinga, Tom W.J.; Eikenboom, Jeroen; Steup-Beekman, Gerda M. (Seminars in Thrombosis and Hemostasis, 2024)
Persistence of serum antiphospholipid antibodies (aPL) is associated with a high thrombotic risk, both arterial and venous, and with pregnancy complications. Due to the potential morbidity and mortality associated with the presence of aPL, identifying and recognizing risk factors for the development of aPL and thrombosis in aPL carriers may help to prevent and reduce the burden of disease. Multiple elements are involved in the pathomechanism of aPL development and aPL-related thrombosis such as genetics, malignancy, and infections. This review will address the role of both well-known risk factors and their evolution, and of emerging risk factors, including COVID-19, in the development of aPL and thrombosis in aPL carriers.
Keywords: antiphospholipid syndrome; antiphospholipid antibody; thrombosis; risk factor